2004
DOI: 10.1186/1472-6963-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Observed-predicted length of stay for an acute psychiatric department, as an indicator of inpatient care inefficiencies. Retrospective case-series study.

Abstract: Background: Length of stay (LOS) is an important indicator of efficiency for inpatient care but it does not achieve an adequate performance if it is not adjusted for the case mix of the patients hospitalized during the period considered. After two similar studies for Internal Medicine and Surgery respectively, the aims of the present study were to search for Length of Stay (LOS) predictors in an acute psychiatric department and to assess the performance of the difference: observed-predicted length of stay, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 38 publications
6
35
1
4
Order By: Relevance
“…Length of stay was measured by total number of days in the program, consistent with previous research (Jiménez, Lam, Marot, & Delgado, 2004).…”
Section: Length Of Staymentioning
confidence: 81%
“…Length of stay was measured by total number of days in the program, consistent with previous research (Jiménez, Lam, Marot, & Delgado, 2004).…”
Section: Length Of Staymentioning
confidence: 81%
“…Previous studies 17,[21][22][23][24] have also shown that older age, cognitive impairment, 23,24 functional dependence, 23 as well as the presence of multiple comorbidities and physical illnesses 25 were associated with longer hospital LOS for psychiatric patients. Additionally, diagnoses of schizophrenia, 26,27 psychotic or mood disorders, 21,22 and the presence of aggression or agitation 26 are associated with longer hospital stays.…”
mentioning
confidence: 99%
“…Additionally, diagnoses of schizophrenia, 26,27 psychotic or mood disorders, 21,22 and the presence of aggression or agitation 26 are associated with longer hospital stays. Our study's objective was to describe psychiatric patients occupying acute beds in a psychiatric unit and based on their needs, to determine the level of care required (acute, compared with nonacute) at day 30 of hospitalization.…”
mentioning
confidence: 99%
“…Es importante destacar que dos terceras partes de la muestra estuvo recibiendo combinación de fármacos por vía oral (antipsicóticos típicos y atípicos, ansiolíticos, entre otros), sin embargo, en el trabajo de Jiménez et al (13) a pesar de tomar como factor predictor el uso de psicotrópicos prevalece el de antipsicóticos solos en un 38,5 % asumiendo que no da lugar a combinaciones posteriores, lo cual resulta incomparable a nuestros hallazgos. Nuestro estudio en función a la evolución favorable de los pacientes, deja una vez más abierta la posibilidad de que el factor más importante asociado a la estancia hospitalaria, no es el factor clínico, sino que, a pesar del buen manejo de los pacientes y su evolución favorable, se atribuyen factores sociales, personales y judiciales, principalmente, que escapan al control del equipo de salud del personal y por ende al cumplimiento de los estándares establecidos para una adecuada estancia hospitalaria, concordando también con los hallazgos de Cheng (14) , pero contrapuesto a Anderson (15) y Øiesvold (16) , que dan mayor importancia a la complejidad clínica (por ejemplo, estados psicóticos y admisiones planificadas) y no otros factores.…”
Section: Discussionunclassified